Somalia (International Monetary Fund, 2021)
The purpose of the missions of Phase I was to develop a functional central bank, including establishing a modern banking supervisory regime. Especially, MCM provided TA missions under the Phase I that have focused on operationalizing banking license capacity, development of on and offsite supervisory capability, and other relevant areas
10.5089/9781513575834.002
Keywords: Graue Literatur; risk rating system; audit report; bank ownership; Somali bank; banks in Somalia; bank's governance; CBS management; CBS directive; Mobile banking; Islamic banking; Bank licensing; Commercial banks; Bank regulation; International Agreements and Observance; International Organizations; Monetary Systems; Standards; Regimes; Government and the Monetary System; Payment Systems; Other Economic Systems: Public Economics; Financial Economics; Financial Institutions and Services: Government Policy and Regulation; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Monetary economics; International institutions; Computer applications in industry & technology; Banking; Financial services law & regulation; International organization; Money and Monetary Policy; Technology; International Economics; Financial services; Industries: Financial Services; Financial regulation and supervision; Banks and Banking; Financial institutions; Islamic Banking and Finance; Monetary policy; International agencies; Banks and banking; Mobile; Banks and banking; Islamic countries; Banks and banking; State supervision; Banks and banking; Monetary Policy